2014
DOI: 10.1177/0004867414560650
|View full text |Cite
|
Sign up to set email alerts
|

The use of clinical and biological characteristics to predict outcome following First Episode Psychosis

Abstract: Objective: Psychotic illnesses such as schizophrenia and other non-affective psychoses are heterogeneous in disease course and functional outcomes. We review evidence from investigations in clinical psychiatry, neuroimaging, neurocognition, and blood biomarker research suggesting that distinct bio-psycho-social patterns exist at the onset and during the early phase of a First Episode Psychosis (FEP), which can describe the risk of individual illness progression and functional trajectories.Method: A selective l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 95 publications
(158 reference statements)
3
25
0
Order By: Relevance
“…Overall, our study found similar predictors of functioning levels in people suffering from first-episode psychosis as in western studies with younger cohorts of subjects, in which gender, 2,5-7 educational attainment, [6][7][8][9] psychopathology 2,4,5,7,12,13,16-20 and baseline functioning 21 were found to be important predictors of longer-term functioning. However, we failed to demonstrate any relationship between age and duration of untreated psychosis with functional outcomes, a finding shared by some overseas studies.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Overall, our study found similar predictors of functioning levels in people suffering from first-episode psychosis as in western studies with younger cohorts of subjects, in which gender, 2,5-7 educational attainment, [6][7][8][9] psychopathology 2,4,5,7,12,13,16-20 and baseline functioning 21 were found to be important predictors of longer-term functioning. However, we failed to demonstrate any relationship between age and duration of untreated psychosis with functional outcomes, a finding shared by some overseas studies.…”
Section: Discussionsupporting
confidence: 81%
“…However, we failed to demonstrate any relationship between age and duration of untreated psychosis with functional outcomes, a finding shared by some overseas studies. 4,6,10,11,15 The lack of predictive value of duration of untreated psychosis in this sample and some other recent studies, was likely due to the fact that the duration of untreated psychosis had been shortened significantly with the introduction of early intervention service, making it less likely to detect a difference in functioning due to variations in the duration of untreated psychosis.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…From these publications the full text was screened, resulting in five more exclusions from the sample for different reasons (i.e. papers presenting a biomedical model [32], a prediction model [33], or that did not include diagnostics or personalized risk estimations [34][35][36]). Analyzing the full text of the included articles resulted in an enrichment of the sample with 13 additional publications by cross-referencing.…”
Section: Resultsmentioning
confidence: 99%